1993
DOI: 10.1037/0003-066x.48.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Depression in adolescence.

Abstract: Adolescence is an important developmental period for understanding the nature, course, and treatment of depression. Recent research concerned with depressive mood, syndromes, and disorders during adolescence is reviewed, including investigations of the prevalence, course, risk factors, and prevention and treatment programs for each of these three levels of depressive phenomena in adolescence. A broad biopsychosocial perspective on adolescent depression is recommended, and possible directions for future integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
411
4
17

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 671 publications
(466 citation statements)
references
References 140 publications
28
411
4
17
Order By: Relevance
“…Between 20% and 50% percent of adolescents report experiencing subsyndromal levels of depression (Kessler, Avenevoli, & Merikangas, 2001;Petersen, Compas, Brooks-Gunn, & Stemmler, 1993). Lifetime prevalence rates of 1.5% (e.g., Costello et al, 1996) and 7% (e.g., Kessler et al, 2005) have been reported for depressive disorders among children and adolescents, respectively.…”
Section: Development Of Depressionmentioning
confidence: 99%
“…Between 20% and 50% percent of adolescents report experiencing subsyndromal levels of depression (Kessler, Avenevoli, & Merikangas, 2001;Petersen, Compas, Brooks-Gunn, & Stemmler, 1993). Lifetime prevalence rates of 1.5% (e.g., Costello et al, 1996) and 7% (e.g., Kessler et al, 2005) have been reported for depressive disorders among children and adolescents, respectively.…”
Section: Development Of Depressionmentioning
confidence: 99%
“…Trois classifications sont utilisées dans les écrits scientifiques afin d'évaluer et catégoriser (hiérarchiser) le phénomène dépressif à l'adolescence : soit le symptôme, le syndrome et le désordre dépressif (Angold, 1988;Angold, Costello & Worthman, 1998;Cantwell & Baker, 1991;Compas, 1997;Kolvin & Sadowski, 2001;Kovacs, 1989;Petersen, Compas, Brooks-Gunn, Stemmler, Ey & Grant, 1993). Le symptôme, le syndrome et le trouble dépressif reflètent la progression non inéluctable du phénomène dépressif .…”
Section: Définition Et Classification De La Dépressionunclassified
“…En ce qui concerne l'humeur dépressive des adolescents, Petersen, Compas, Brooks-Gunn, Stemmler, Ey et Grant (1993) relèvent des différences au niveau du genre.…”
Section: La Dépression Et Les Différences Liées Au Genre Chez Les Adounclassified
“…Although studies of psychiatric disorders during adolescence have found a fairly low incidence of moderate to severe depression, in those who are affected the symptoms may be life-threatening (Peterson, Compas, Brooks-Gun, Stemmler, Ey & Grant, 1993). …”
Section: Effects Of Parental Divorce On Adolescent Childrenmentioning
confidence: 99%